SURVEY TERESTRIS PENGUKURAN JARING KONTROL HORIZONTAL ORDE-4 DENGAN MENGGUNAKAN METODE POLIGON TERTUTUP - mutrofin rozaq; lukito kurniawan (Prokons: Jurnal Teknik Sipil, 2019)
Construction of the Lumajang PDD campus building, the pilot of the Lumajang Community Community Academy began in 2017. The campus building will be built on 5.3 hectares of land located on Lumajang East Road. The process of building construction, will begin with measuring the boundary of the land by placing coordinates. This research was conducted in order to prepare the location or location of horizontal control points in preparation for the establishment of the Lumajang Community Community Academy campus building.The research method used in measuring coordinate points is the polygon method. Measurements were carried out in terrestrial surveys using theodolite devices. Theodolite devices are among the measurement target points, namely back-face. The measurement target points are located at the specified land boundary. The results of the study obtained a map of the distribution of horizontal control points on the boundaries of campus land and the installation of monuments